2017
DOI: 10.1136/jech-2016-208513
|View full text |Cite
|
Sign up to set email alerts
|

Association between income trajectories in childhood and psychiatric disorder: a Swedish population-based study

Abstract: Findings show that children growing up in a household characterised by low or decreasing family income have an increased risk for psychiatric disorder. Continued work is needed to reduce socioeconomic inequalities in psychiatric disorders. Policies and interventions for psychiatric disorders should consider the socioeconomic background of the family as an important risk or protective factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
3
30
1
Order By: Relevance
“…Furthermore, a recent large study in Sweden has also shown higher rates of mental disorders in individuals with a steady low or downward income trajectory [9]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a recent large study in Sweden has also shown higher rates of mental disorders in individuals with a steady low or downward income trajectory [9]. …”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in the same city in Southern Brazil with the 1993 Pelotas Birth Cohort at age 15, Anselmi et al also found that those individuals who belonged to better-off families and later became impoverished presented higher prevalence of conduct problems than those from better-off families [ 40 ]. Furthermore, a recent large study in Sweden has also shown higher rates of mental disorders in individuals with a steady low or downward income trajectory [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest risk, however, was observed amongst those whose familial income remained consistently low. 24 In the UK, transition into income poverty during early childhood has been linked with raised risk for socioemotional behavioural problems in middle childhood. 3 Research from the USA 25 has also found that a large fall in familial income during infancy was associated with behavioural problems in later childhood.…”
Section: Self-harmmentioning
confidence: 99%
“…The timing of exposure to childhood social adversity may therefore be of relevance in relation to future mental-health problems. Previous research examining the issue of timing has primarily focused on more severe childhood social adversities in relation to later mental-health problems [21] or psychiatric disorders [22,23]. To our knowledge, few studies [10,16,24] have examined the timing of childhood low SEP in relation to later depressive symptoms in adolescence and early adulthood.…”
Section: Introductionmentioning
confidence: 99%